2022
DOI: 10.33394/jollt.v10i2.4510
|View full text |Cite
|
Sign up to set email alerts
|

‘Is the Picture Worth a Thousand Words?’: the Interpersonal Meanings of a Dialogue in an Efl Textbook

Abstract: This study was aimed at scrutinising a multimodal text embedded in a dialogue of an EFL textbook. To this end, Systemic Functional Multimodal Discourse Analysis (SF-MDA) focused on interpersonal meanings consulting grammar of visual design and intersemiotic complementarity drawing on systemic functional linguistics were employed to analyse the artefact, a dialogue within a part named 'communication' taken from an EFL textbook for a primary school level. The findings revealed that declarative clause and modalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…They confirmed that SFL analysis could shed light on EFL textbooks' genre and register features, enabling teachers to design materials that reflect authentic language use in real-world contexts. Recent studies have also stressed the importance of incorporating multimodal texts in EFL textbooks (Montes, Barboza, & Olascoaga, 2014), integrating grammatical structures that support the ideational and interpersonal functions of the texts (Sugianto, Prasetyo, & Asti, (2022), considering the impact of SFL on language teaching (Rezeg, 2022;Zhang, 2017), and incorporating critical thinking elements within EFL textbooks (Wang, 2020). Collectively, these studies emphasize the significance of employing an SFL-based approach to evaluate and modify EFL textbooks, considering learners' diverse needs, and incorporating multimodal and critical thinking components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They confirmed that SFL analysis could shed light on EFL textbooks' genre and register features, enabling teachers to design materials that reflect authentic language use in real-world contexts. Recent studies have also stressed the importance of incorporating multimodal texts in EFL textbooks (Montes, Barboza, & Olascoaga, 2014), integrating grammatical structures that support the ideational and interpersonal functions of the texts (Sugianto, Prasetyo, & Asti, (2022), considering the impact of SFL on language teaching (Rezeg, 2022;Zhang, 2017), and incorporating critical thinking elements within EFL textbooks (Wang, 2020). Collectively, these studies emphasize the significance of employing an SFL-based approach to evaluate and modify EFL textbooks, considering learners' diverse needs, and incorporating multimodal and critical thinking components.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the use of nominal groupings enhances our comprehension of how language is organized and structured consistently and coherently within texts. The systemic functional features of SFL encompass language's ideational, interpersonal, and textual functions, offering a comprehensive framework for language analysis (Darong, 2022b;Tian, 2020;Sugianto et al, (2022). This framework could evaluate how language is utilized in EFL textbooks to convey meaning, create cohesion and coherence, and achieve specific communication goals.…”
Section: Introductionmentioning
confidence: 99%